Ischemia–Reperfusion Injury and Immunosuppressants Promote Polyomavirus Replication Through Common Molecular Mechanisms - Chen, Xu-Tao; Huang, Yang; Wang, Jing; Li, Ge; Zhang, Yu; He, Li-Fang; Lian, Yue-Xiao; Yang, Shi-Cong; Zhao, Guo-Dong; Zhang, Hui; Qiu, Jiang; Zhang, Lei; et al. (Frontiers in Immunology, 2022)
Background BK polyomavirus (BKPyV)-associated nephropathy (BKPyVAN) causes renal allograft dysfunction and graft loss. However, the mechanism of BKPyV replication after kidney transplantation is unclear. Clinical studies have demonstrated that immunosuppressants and renal ischemia–reperfusion injury (IRI) are risk factors for BKPyV infection. Studying the pathogenic mechanism of BKPyV is limited by the inability of BKPyV to infect the animal. Mouse polyomavirus (MPyV) is a close homolog of BKPyV. We used a model of MPyV infection to investigate the core genes and underlying mechanism of IRI and immunosuppressants to promote polyomavirus replication. Materials and Methods One-day-old male C57BL/6 mice were intraperitoneally injected with MPyV. At week 9 post-infection, all mice were randomly divided into IRI, immunosuppressant, and control groups and treated accordingly. IRI was established by clamping the left renal pedicle. Subsequently, kidney specimens were collected for detecting MPyV DNA, histopathological observation, and high-throughput RNA sequencing. Weighted gene correlation network analysis (WGCNA), protein–protein interaction network analysis, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis were used to screen for core genes and common signaling pathways involved in promoting MPyV replication by IRI and immunosuppressants. Results After primary infection, MPyV established persistent infection in kidneys and subsequently was significantly increased by IRI or immunosuppressant treatment individually. In the IRI group, viral loads peaked on day 3 in the left kidney, which were significantly higher than those in the right kidney and the control group. In the immunosuppressant group, viral loads in the left kidney were significantly increased on day 3, which were significantly higher than those in the control group. Protein–protein interaction network analysis and WGCNA screened complement C3, epidermal growth factor receptor (EGFR), and FN1 as core genes. Pathway enrichment analysis based on the IRI- or immunosuppressant-related genes selected by WGCNA indicated that the NF-κB signaling pathway was the main pathway involved in promoting MPyV replication. The core genes were further confirmed using published datasets GSE47199 and GSE75693 in human polyomavirus-associated nephropathy. Conclusions Our study demonstrated that IRI and immunosuppressants promote polyomavirus replication through common molecular mechanisms. In future studies, knockdown or specific inhibition of C3, EGFR, FN1, and NF-κB signaling pathway will further validate their critical roles in promoting polyomavirus replication.